Pengaruh Brand Ambassador Dan Brand Image Terhadap Keputusan Pembelian Dengan Trustworthiness Sebagai Variabel Intervening - Kristian, Galih; Welsa, Henny; Udayana, Ida Bagus Nyoman (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine the effect of brand ambassador and brand image on purchasing decisions with trustworthiness as an intervening variable in the Yogyakarta Starcross distribution. the type of research used in this research is descriptive quantitative. The population used is the customer of the Starcross Yogyakarta distribution as many as 100 people. The sample used in this study is 100 customers using the sampling technique used is non-probability sampling using a data collection method using a questionnaire. The data analysis technique in this study used multiple linear regression. Based on the results of this study, brand ambassadors have a significant positive effect on purchasing decisions, brand image has a significant positive effect on purchasing decisions, brand ambassadors have a significant positive effect on trustworthiness, brand image has a significant positive effect on trustworthiness, trustworthiness has a significant positive effect on purchasing decisions. In this case, trustworthiness as an intervening variable is able to mediate the relationship between brand ambassadors on purchasing decisions, and brand image on purchasing decisions.